Hybridization of a triple-effect absorption heat pump with a humidification-dehumidification desalination unit: Thermodynamic and economic investigation. (1st April 2021) - Elbassoussi, Muhammad H.; Antar, M.A.; Zubair, Syed M.
Highlights: A LiBr absorption chiller combined with an HDH desalination unit is investigated. A low-grade (natural gas) energy source is utilized to operate the main system. Results reveal that the proposed system produces 10 kg/h of fresh water at 0.85 ȼ/l. The system can also produce a cooling capacity of 2.0 kW at a COP value of 1.5. The proposed system shows comparable performance to other hybrid HDH systems. Abstract: In this study, a novel hybrid desalination/cooling system is investigated. The system combines a triple-effect absorption (TEAB) heat pump (whose working fluid is LiBr/water solution) and a water-heated humidification dehumidification (HDH) desalination unit. The system is investigated for simultaneous production of freshwater and cooling effect. A low-grade energy source (natural gas) is utilized to operate the system, while solar PV panels are used to power the auxiliary components of the system, such as pumps and blowers. A detailed mathematical model is established to explore the influence of different parameters on the thermodynamic and economic performance of the system. From the HDH unit's side, it is observed that the effectiveness of the HDH components (dehumidifier and humidifier), the mass flow rate ratio, and the inlet conditions of the saline water have a considerable impact on the system performance. On the other hand, from the TEAB system's side, the performance of the hybrid system is found to be significantly affected by the effectiveness of both the solution heat exchangers and the absorber. The results reveal that the system can produce, at its optimal operating conditions, 10 kg of fresh water per hour for 0.85 ȼ/l with a gained-output-ratio (GOR) value approaching 5.0. Additionally, the system can produce a cooling capacity of about 2.0 kW at a coefficient of performance (COP) value close to 1.5. Furthermore, the proposed TEAB-HDH system shows comparable performance to other heat-pump-powered HDH systems available in the literature.